Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1111/jvim.13923
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clinical Metrology Instrument in Dogs with Osteoarthritis

Abstract: BackgroundIn veterinary clinical pain studies, there is a paucity of data on test‐retest variability in Clinical Metrology Instruments (CMIs), and it is unknown whether CMIs should be administered using independent (respondents not permitted to see previous answers) or dependent (respondents shown previous answers) interviewing.ObjectivesTo compare baseline variability in CMIs designed to assess pain in dogs with osteoarthritis, and compare CMI scores using independent (InD) and dependent interviewing (DI) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 24 publications
0
40
0
Order By: Relevance
“…The validated LOAD questionnaire was used as a subjective outcome measure . Owners reported that all dogs had an improved score.…”
Section: Discussionmentioning
confidence: 99%
“…The validated LOAD questionnaire was used as a subjective outcome measure . Owners reported that all dogs had an improved score.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, clinical metrology instruments and a patient-centred approach to outcome assessment have become mainstays in the assessment of human OA. A patient-centred approach has also been incorporated into veterinary assessments; clinical metrology instruments and validated outcome questionnaires are used to capture pain-related behaviour over long periods of time in home environments 164 , and pet owners can provide proxy assessments, just as parents or caregivers would for young children or adults with dementia 165,166 . Although objective assessment methods are less readily available than proxy reporting, these instruments have been validated, they are inexpensive and are straightforward to use, the data they produce are easy to analyse, and they do not have the relevancy issues associated with proxy reporting.…”
Section: A Means To Identify the Genetic Basis Of Analogous Diseasementioning
confidence: 99%
“…It is still unknown if respondents should be permitted or not to see previous answers. Previous reports show little difference has been observed between both approaches, but allowing responders to see previous answers results in increased treatment effect sizes, which may increase clinical trial power [47]. In this study, in order to reduce bias, trainers were not allowed to see previous answers, as it might influence their responses, particularly with a long follow-up period.…”
Section: Discussionmentioning
confidence: 99%